2010
DOI: 10.1159/000316069
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Device-Associated Actinomycosis of the Ovary and Urinary Bladder: A Case Report

Abstract: Actinomycosis of the urinary bladder is rare, mostly subsequent to abdomino-pelvic infection, and usually affects women with long-term use of an intrauterine device. We describe a case of vesical actinomycosis mimicking a papillary bladder tumour in a 56-year-old woman with primary manifestation of the disease in the genital tract, subjected to two transurethral resections after relapse of a polypoid mass in the bladder. Urological procedures are necessary to differentiate actinomycosis from bladder cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…While the organism can be found as a normal flora inhabiting the oral and gastrointestinal tract in normal people, clinical actinomycosis occurs most commonly in the cervicofacial (~60%), abdomino-pelvic (22%) and thoracic (15%) regions [1,3,[4][5][6]7]. Actinomycosis rarely involves the genito-urinary system and it is usually secondary to abdomino-pelvic infection [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the organism can be found as a normal flora inhabiting the oral and gastrointestinal tract in normal people, clinical actinomycosis occurs most commonly in the cervicofacial (~60%), abdomino-pelvic (22%) and thoracic (15%) regions [1,3,[4][5][6]7]. Actinomycosis rarely involves the genito-urinary system and it is usually secondary to abdomino-pelvic infection [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cases of actinomycosis have been reported relating to female pelvic actinomycosis and the use of an IUD [1,5,[7][8][9]. One study has identified ninety-two cases of actinomycotic abscesses associated with retained IUD or intravaginal foreign bodies with an average of 8 years in situ while less than 16% of the cases had IUD for less than 3 years [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On macroscopic examination, these effusions range from serosanguinous to densely purulent, and cytology may not always detect the bacteria . Microbiologic cultures may be confirmatory, although for Actinomyces , only a minority of cultures return positive results …”
Section: Cytopathology Of Nocardia and Actinomyces On Exfoliative Spementioning
confidence: 99%
“…However, primary vesical actinomycosis is an extremely rare entity with a total of 10 cases reported in the literature to date . More frequently, actinomycosis involving the urinary bladder occurs secondary to direct extension from a primary infectious source in a neighboring pelvic organ . Jang et al reported a single patient with the initial diagnosis of primary vesical actinomycosis made on routine urine cytology .…”
Section: Cytopathology Of Nocardia and Actinomyces On Exfoliative Spementioning
confidence: 99%